An (R)-Selective Transaminase From Thermomyces stellatus: Stabilizing the Tetrameric Form - Heckmann, Christian M.; Gourlay, Louise J.; Dominguez, Beatriz; Paradisi, Francesca (Frontiers in Bioengineering and Biotechnology, 2020)
The identification and 3D structural characterization of a homologue of the (R)-selective transaminase (RTA) from Aspergillus terreus (AtRTA), from the thermotolerant fungus Thermomyces stellatus (TsRTA) is here reported. The thermostability of TsRTA (40% retained activity after 7 days at 40°C) was initially attributed to its tetrameric form in solution, however subsequent studies of AtRTA revealed it also exists predominantly as a tetramer yet, at 40°C, it is inactivated within 48 hours. The engineering of a cysteine residue to promote disulfide bond formation across the dimer-dimer interface stabilized both enzymes, with TsRTA_G205C retaining almost full activity after incubation at 50 °C for 7 days. Thus, the role of this mutation was elucidated and the importance of stabilizing the tetramer for overall stability of RTAs is highlighted. TsRTA accepts the common amine donors (R)-methylbenzylamine, isopropylamine, and d-alanine as well as aromatic and aliphatic ketones and aldehydes.